2005
DOI: 10.1007/s00415-005-0728-9
|View full text |Cite
|
Sign up to set email alerts
|

Corticomotor organisation and motor function in multiple sclerosis

Abstract: Our objective was to determine whether there are changes in the corticomotor map for the hand in multiple sclerosis, and whether these changes correlate with indices of motor function and measures of corticomotor conduction or excitability. Transcranial magnetic stimulation (TMS) maps, motor evoked potential (MEP) latency and amplitude, motor threshold and EDSS and Purdue-pegboard measurements were made in 26 subjects with relapsing-remitting multiple sclerosis. Correlations were sought between these measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…It is known that there can be a relationship between motor impairment and corticomotor conduction in MS [3,21]. Although MEP amplitude and MVC force were somewhat reduced at baseline in our MS group, other parameters of corticomotor conduction (MEP threshold, latency and duration) were not greatly different from controls, indicating that the MS group were only mildly affected at the time of the study.…”
Section: Discussioncontrasting
confidence: 57%
“…It is known that there can be a relationship between motor impairment and corticomotor conduction in MS [3,21]. Although MEP amplitude and MVC force were somewhat reduced at baseline in our MS group, other parameters of corticomotor conduction (MEP threshold, latency and duration) were not greatly different from controls, indicating that the MS group were only mildly affected at the time of the study.…”
Section: Discussioncontrasting
confidence: 57%
“…The contrasts between ventilation in unanesthetized, and phrenic activity in anesthetized les rats suggests two likely sites of dysfunction: 1) alterations in supra-pontine inputs to brainstem respiratory neurons and 2) alterations in vagal afferent processing within the brainstem. The former is consistent with impaired corticomotor function associated with demyelination in MS patients (Thickbroom et al, 2005). The involvement of vagal afferent neurons, and their primary site of termination in the nucleus of the solitary tract (NTS) in modulating breathing timing are well known (Kubin et al, 2006).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, these sensory pathways were intact in the unanesthetized plethysmography experiments, possibly accounting for the difference in experimental results between conditions. On the other hand, cortical demyelination is associated with desynchronization of electrical activity and impaired corticomotor function with associated fatigue and heightened perception of effort required for motor activity in humans (Petajan and White, 2000; Perretti et al, 2004; Liepert et al, 2005; Thickbroom et al, 2005, 2006; for review see: Zwarts et al, 2008). Although we cannot comment on perception in our awake les rats (Banzett et al, 2008), it is possible that dysmyelination of the motor cortex or the cortical integrative pathways may be associated with the mechanisms underlying respiratory impairment during plethysmography experiments in the older les rats.…”
Section: Discussionmentioning
confidence: 99%
“…The precise relationship between MEP amplitude and the development of fatigue is not certain, but an increase in MEP amplitude may reflect a change in the balance of intracortical excitation and inhibition that could underlie central adaptive processes directed at maintaining task performance as fatigue develops. We have also previously shown that there are changes in the corticomotor map of the hand in MS which are correlated with clinical and motor measures [15], further highlighting the role of neural plasticity in compensating for the effects of demyelination in MS. MS and control subjects were able to maintain task performance across bouts, but tap-rate declined within each of the exercise periods. Thus each 45 second interbout resting period was sufficient to restore performance, and tap rate at the outset of each bout of exercise actually increased across bouts.…”
Section: Discussionmentioning
confidence: 93%